Experimental, Theoretical and CFD Validations for Solar Powered Atmospheric Water Generation Using Thermoelectric Technics - Alsheekh, Mohammed; Najim, Saleh E.; Sultan, Hussein S. (Basrah Journal for Engineering Sciences, 2021)
The Atmospheric Water Generator (AWG) is an environmental water recovery that easily dehumidifies water vapor moisture from the air. This article presents an experiment to construct an AWG model using solar energy as a source of power. An experimental and numerical study for a device of (AWG) is performed. The experimental work is performed at Basrah city, located in the south of Iraq, during August and September of 2019 and March of 2020. The theoretical results are calculated by EES and the numerical study has been conducted by the (ANSYS19/CFD/ FLUENT) program. The experimental device is tested for different days with different climate conditions. The Maximum water production obtained is 3.4 L/day from all the testing days, for different hours of operation when the relative humidity in the range of (45 – 95 %) and the temperature range from 17 °C to 45 °C. The results shown that, the water production rate is increased with increasing humidity, temperatures, hours of operation, and model size.